Digitalization of inclusive education: approaches to management and policy initiatives at the state and municipal levels - Tatiana N. Bun; Yulia S. Kuznetsova; Victoria R. Zayec (RUDN Journal of Public Administration, 2025)
This study examines the changing landscape of inclusive education in the era of digital transformation, with a special focus on the innovative role of media classes. Designed to provide equal learning opportunities for students with disabilities, inclusive education aims to ensure accessibility while promoting meaningful social integration. Media classes are an example of this approach, using digital platforms and adaptive technologies to create a personalized learning environment that meets the diverse needs of students. These classes provide access to advanced tools and resources that support both academic achievement and the development of basic practical skills, including digital literacy and multimedia content creation. The discussion highlighted how digital platforms enhance the quality of education through features such as accessibility, personalized learning paths and increased engagement. Tools such as screen readers, text-to-speech technologies, and learning management systems enable students to interact with educational content in a way that suits their specific sensory, cognitive, or physical needs. By encouraging autonomy and independent learning, these technologies enable students to organize their own educational journeys. However, the study also examines the problems that hinder the full integration of digital technologies into inclusive education. Insufficient infrastructure, inadequate teacher training and limited financial resources are identified as the main obstacles. The need for strategic planning in infrastructure development, teacher training and curriculum innovations is emphasized to ensure the effective implementation of inclusive practices. The study concludes by highlighting the significant social and professional benefits of integrating digital technologies into inclusive education. By providing students with disabilities with the skills and knowledge they need to succeed in an increasingly digital world, these initiatives not only expand individual potential, but also contribute to a more inclusive and equitable society. The study calls for an active policy and continuous efforts to support the continuous development of inclusive educational systems.